2012
DOI: 10.4172/2155-6199.1000161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Quality Index For Drinking Purposes In The Case of Damodar River, Jharkhand and West Bengal Region, India

Abstract: Damodar River is one of the most important fresh water source in Jharkhand and West Bengal. Its water is used for drinking by the growing population and also used in allied Industries situated down the stretch. The water quality is being reducing day by day due to heavy input of sewage and wastes from industrial effluents, cattle stock breeding, irrigation and human activities etc. Therefore, an attempt has been made to assess the quality of water in relation to know the pollution load in terms of biological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…In the recent years, many applied research on water quality had been conducted and they have brought the reasons behind the deterioration of water quality such as urban sewage and discharge of industrial effluents from the iron and steel industries, chemical, cement, tannery industry, thermal power plant. The contemporary research highlighted that industrial waste effluents are directly thrown into the river water without treatment ( Bhattacharyya et al 2013 ; Sundararanjan and Mohan 2011 ; Ghosh and Banerjee, 2012 ; Singh et al 2014 ; Chatterjee et al 2010 ; George et al 2010 ; Mukherjee et al 2012 ). Here, the current study focused that the physical, chemical and heavy metals have been found beyond permissible limit (WHO, 2011 ) at effluents discharge sites in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, many applied research on water quality had been conducted and they have brought the reasons behind the deterioration of water quality such as urban sewage and discharge of industrial effluents from the iron and steel industries, chemical, cement, tannery industry, thermal power plant. The contemporary research highlighted that industrial waste effluents are directly thrown into the river water without treatment ( Bhattacharyya et al 2013 ; Sundararanjan and Mohan 2011 ; Ghosh and Banerjee, 2012 ; Singh et al 2014 ; Chatterjee et al 2010 ; George et al 2010 ; Mukherjee et al 2012 ). Here, the current study focused that the physical, chemical and heavy metals have been found beyond permissible limit (WHO, 2011 ) at effluents discharge sites in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the waste effluents, heavy metals, toxic elements from nearby industries have been discharged into the river and lowering water quality as well as river ecosystem. Many contemporary researches on water quality of Damodar have been conducted through various modern methods and techniques (Tiwari and Dhar 1994 ; Basu and Mitra, 2002 ; Tiwari and Abhishek 2005 ; George et al 2010 ; Chatterjee et al 2010 ; Banerjee and Gupta 2012 ; Mukherjee et al 2012 ). These relevant studies (physical, chemical or biological assessment) were conducted through popular methods such as water quality index (WQI), pollution load index (PLI), enrichment factor (EF), aseptic techniques (microbial analysis), descriptive statistics, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Here, WQI comprises of sub-indices allotted to each parameter as per its importance and all together of sub-indices expressed in a single value which is indicating water quality (Sharma et al 2020b). The WQI method is widely used by many researchers for the assessment of water quality in different parts of the world (Swami and Tyagi 2000;Kanakiya et al 2015;Dwivedi and Pathak 2007;Mukherjee et al 2012;Selvam et al 2014;Hou et al 2016). Quality of water is also indicated by the health as well as the growth of plants and aquatic animals in the aquatic ecosystem or environment.…”
Section: Introductionmentioning
confidence: 99%
“…These industrial effluents or wastes include heavy metal ions, oils, greases, acids, dissolved inorganic, pesticides, polychlorinated biphenyls (PCBs), dioxins, polyaromatic hydrocarbons (PAHs), petrochemicals, phenolic compounds, and microorganisms. The contemporary studies focused that the untreated industrial effluents and urban sewage are being discharged into the main river Damodar and its tributaries, and as a result, the quality of water has been drastically reduced (De et al 1980;Tiwary and Abhishek 2005;George et al 2010;Chatterjee et al2010;Mukherjee et al 2012;Banerjee and Gupta 2013;Pal and Maiti 2018;Savichev et al 2020;Chakraborty et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Except S 5 all samples were contains more DO values because of domestic sewage effluents and dumping of garbage, Table-8. This causes microbiological contamination consuming the DO [6].…”
Section: Assessment Of Water Quality Index In Subarnarekha River Basimentioning
confidence: 99%